Effects of Peer Support Interventions on the Communication of Preschoolers with Autism Spectrum Disorder: A Systematic Review - Chapin, Shelley; McNaughton, David; Boyle, Susannah; Babb, Salena (Seminars in Speech and Language, 2018)
Many young children with autism spectrum disorders (ASDs) experience difficulty in the development of communication skills. Teaching peers to make use of communication support behaviors has been investigated as a strategy to increase communication for young children with ASD in early childhood settings. The purpose of this systematic review was to examine (1) the overall effects of peer support interventions on the communication of young children with ASD and (2) any possible moderating variables related to participant and intervention characteristics. The social support model was used as a framework for the study of intervention components. Eighteen single-case experimental design studies (48 children with ASD) met the inclusion criteria and were advanced to the full coding and analysis phase of the investigation. Descriptive analyses and effect size estimations using the improvement rate difference (IRD) metric were conducted. Overall, peer support interventions were found to be effective across a range of young children with ASD and intervention approaches. Evidence was also identified for the use of the social support model as a framework to guide the development of peer interventions in early childhood settings. The use of friendship groups, the selection of play materials based on the interests of the child with ASD, and the provision of augmentative and alternative communication appeared to be associated with positive communication outcomes.
Keywords: children with ASD; peer support interventions; communication; early childhood